Tension orbit secondary to a carious primary molar—A case report. Issue 4 (16th February 2021) - Jaisani, Mehul R.; Dongol, Ashok; Acharya, Pradeep; Yadav, Anjani Kr; Pasvan, Chandrakant; Rai, Siddhartha; Pande, Rikta; Koirala, Bandana; Shah, Shankar; Lavaju, Poonam; Laverick, Sean
Abstract: Though rare, a pediatric dentist should have background knowledge of this kind of presentation which can greatly affect their patient's quality of life and leave them with a significant deficit at a very young age. Abstract : Though rare, a pediatric dentist should have background knowledge of this kind of presentation which can greatly affect their patient's quality of life and leave them with a significant deficit at a very young age.